I want to solve for $\gamma$ in the following equation:

$$ \frac{1-e^{-2\cdot 10^{-3}\gamma}}{1+e^{-2\cdot 10^{-3}\gamma}}=1.54e^{i0.24\pi} $$

Attempt: \begin{align} 1-e^{-2\cdot10^{-3}\gamma}&=1.54e^{i0.24\pi}(1+e^{-2\cdot 10^{-3}\gamma}) \\ &=1.54e^{i0.24\pi}+1.54e^{i0.24\pi}e^{-2\cdot 10^{-3}\gamma} \end{align} \begin{align} 1-e^{-2\cdot10^{-3}\gamma}-1.54e^{i0.24\pi}e^{-2\cdot 10^{-3}\gamma} =1.54e^{i0.24\pi} \end{align} \begin{align} 1-e^{-2\cdot 10^{-3}\gamma} (-1-1.54e^{i0.24\pi}) =1.54e^{i0.24\pi} \end{align} \begin{align} -e^{-2\cdot 10^{-3}\gamma} (-1-1.54e^{i0.24\pi}) =1.54e^{i0.24\pi}-1 \end{align} \begin{align} e^{-2\cdot 10^{-3}\gamma} (-1-1.54e^{i0.24\pi}) =-1.54e^{i0.24\pi}+1 \end{align} \begin{align} e^{-2\cdot 10^{-3}\gamma} = \frac{-1.54e^{i0.24\pi}+1}{-1-1.54e^{i0.24\pi}} \end{align} Stuck with this fraction, how can I simplify it? \begin{align} -2\cdot 10^{-3}\gamma = \ln \bigg (\frac{-1.54e^{i0.24\pi}+1}{-1-1.54e^{i0.24\pi}}\bigg ) \end{align} \begin{align} \gamma =\frac{1}{-2\cdot 10^{-3}} \ln \bigg (\frac{-1.54e^{i0.24\pi}+1}{-1-1.54e^{i0.24\pi}}\bigg ) \end{align}

Correct answer is approximately: $$ 2\cdot 10^{-3}\gamma=\ln (2.24 e^{i0.68\pi}) $$ $$ \gamma= 0.0403+i0.108=0.115 e^{i0.386\pi} $$ Thanks!


1 Answer 1


You can use $e^{i\theta }=\cos \theta + i\sin \theta $, and then multiply and divide by the conjugate of denominator to simplify further.

By the way, it would have been easier to solve, if you had introduced another variables, I.e.

$$e^{-2 \times 10^{-3} \gamma}=t ; \quad 1.54 e^{i 0.24\pi} =k$$

Now rewrite the equation as $$\frac{1-t}{1+t}=k \implies^{\text{(C & D)}} \; t =\frac{1-k}{k+1}$$

And now substitue in terms of $\gamma$ back into obtained equation.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.